2021
DOI: 10.1007/s10661-021-09297-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the effectiveness of a saturated buffer to reduce tile NO3-N concentrations in eastern Iowa

Abstract: a geophysical survey (quantifying low potential for N loss to deeper aquifers), and comparisons to other similar Iowa sites. The study provides more assurance to new adopters that this practice can be installed in many areas throughout the Midwestern Cornbelt region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…An annual NO 3 ‐N tile input to the Frye oxbow exceeded 400 kg on one occasion. The annual tile NO 3 ‐N loading into the oxbows was similar to tile loads draining into other edge‐of‐field remediation practices including saturated buffers reported by Jaynes and Isenhart (2019) (13–179 kg N) and Streeter and Schilling (2021) (75–136 kg N). Our study confirms that reconstructed oxbows should only be considered an agricultural BMP if they are configured to receive tile drainage inputs.…”
Section: Discussionsupporting
confidence: 78%
“…An annual NO 3 ‐N tile input to the Frye oxbow exceeded 400 kg on one occasion. The annual tile NO 3 ‐N loading into the oxbows was similar to tile loads draining into other edge‐of‐field remediation practices including saturated buffers reported by Jaynes and Isenhart (2019) (13–179 kg N) and Streeter and Schilling (2021) (75–136 kg N). Our study confirms that reconstructed oxbows should only be considered an agricultural BMP if they are configured to receive tile drainage inputs.…”
Section: Discussionsupporting
confidence: 78%
“…Perennial plants growing in the buffer intercept the discharge and utilize nutrients contained within the water. Recent research (Streeter & Schilling, 2021) found that saturated buffers reduced nitrate nitrogen (NO 3 -N) concentration in tile drainage from 15 g/L to less than 1.5 mg/L. Saturated buffers work best in locations where the field is sloped less than 1%, there are no layers of sand or gravel, soil organic matter is at least 1% in the upper 30 inches of the soil profile, and the main drains at least 15 ac of land (The Ohio State University, 2021).…”
Section: Featuresmentioning
confidence: 99%
“…Perennial plants growing in the buffer intercept the discharge and utilize nutrients contained within the water. Recent research (Streeter & Schilling, 2021) found that saturated buffers reduced nitrate nitrogen (NO 3 -N) concentration in tile drainage from 15 g/L to less than 1.5 mg/L.…”
Section: Saturated Buffers On Tile-drained Fieldsmentioning
confidence: 99%